Wireless dynamic channel assignment performance under packet data traffic. - Cheng, M. (IEEE Journal on selected areas in communications)
With the increased subscription rate in Internet services and wireless communications services, a significant amount of traffic for the future wireless communications will be from Internet applications. Therefore, it is important to design a bandwidth-efficient channel allocation scheme to support Internet traffic, which are packet-switched in nature. Dynamic channel assignment (DCA) schemes are believed to achieve higher system capacity and spectrum efficiency in a frequency-reuse wireless system without frequency planning. This makes DCA a suitable candidate to provide high-speed wireless packet data services. This paper investigates the performance of two distributed measurement-based DCA schemes under Pareto-distributed packet data traffic, a well-known traffic model with heavy-tailed distribution and infinite variance. Performance comparisons of DCA schemes under different wireless packet data traffic conditions are also presented. The sensitivity of the channel setup delay on the SIR performance at access are discussed. These results can provide guidelines for the future design of DCA and medium access control (MAC) protocols for wireless Internet services